Renal shear wave velocity by acoustic radiation force impulse did not reflect advanced renal impairment. Issue 12 (December 2016) - Takata, Tomoaki; Koda, Masahiko; Sugihara, Takaaki; Sugihara, Shinobu; Okamoto, Toshiaki; Miyoshi, Kenichi; Matono, Tomomitsu; Hosho, Keiko; Mae, Yukari; Iyama, Takuji; Fukui, Takeaki; Fukuda, Satoko; et al.
Abstract: Aim: Acoustic radiation force impulse is a noninvasive method for evaluating tissue elasticity on ultrasound. Renal shear wave velocity measured by this technique has not been fully investigated in patients with renal disease. The aim of the present study was to compare renal shear wave velocity in end‐stage renal disease patients and that in patients without chronic kidney disease and to investigate influencing factors. Methods: Renal shear wave velocities were measured in 59 healthy young subjects (control group), 31 subjects without chronic kidney disease (non‐CKD group), and 39 end‐stage renal disease patients (ESRD group). Each measurement was performed 10 times at both kidneys, and the mean value of eight of 10 measurements, excluding the maximum and minimum values, was compared. Results: Renal shear wave velocity could be measured in all subjects. Renal shear wave velocity in the control group was higher than in the non‐CKD group and in the ESRD group, and no difference was found between the non‐CKD group and the ESRD group. Age and depth were negatively correlated to the renal shear wave velocity. In multiple regression analysis, age and depth were independent factors for renal shear wave velocity, while renal impairment was not. There was no difference between the non‐CKD group and the ESRD group, even when ages were matched and depth was adjusted. Conclusion: Renal shear wave velocity was not associated with advanced renal impairment. However, it reflected alteration of renal aging, and this technique may be useful to detect renal impairment in the earlier stages. Summary at a Glance: This is an interesting report for evaluating kidney tissue elasticity using acoustic radiation force impulse. It seems a simple and non‐invasive method.